Molecular Phylogenetic Analysis: Design and Implementation of Scalable and Reliable Algorithms and Verification of Phylogenetic Properties - Álvarez-Jarreta, Jorge; De Miguel Casado, Gregorio; Mayordomo, Elvira (Jornada de Jóvenes Investigadores del I3A, 2017)
Since the creation of the bioinformatics field, and even more since the creation of the so called nextgeneration sequencing, the relevance of computer methods and technologies has significantly increased. We here present several contributions we have published as solution for different problems involved in the study of the evolution process.